2007
DOI: 10.1530/rep-07-0289
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interleukin-1β regulated genes in uterine smooth muscle cells

Abstract: We analyzed the response of uterine smooth muscle cells to interleukin-1b (IL-1b). We first showed that PHM1-31 myometrial cells, our cellular model, are contractile. To determine the molecular mechanisms of uterine smooth muscle cell activation by proinflammatory cytokines, we performed genechip expression array profiling studies of PHM1-31 cells in the absence and the presence of IL-1b. In total, we identified 198 known genes whose mRNA levels are significantly modulated (O2.0-fold change) following IL-1b ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 54 publications
3
50
0
Order By: Relevance
“…In fact, a positive effect of both IL-1 and TNF␣ has been observed previously in a wide range of cells: endothelial (9,20) and hepatic cells (9), fibroblasts (9,20,23), myoblasts (20), mononuclear phagocytes (3,20), and renal epithelial cells (32). Furthermore, IL-1 was effective in dendritic (12) and smooth muscle cells (11) and TNF␣ in 3T3-F442A adipocytes (1), synoviocytes (26), and lung epithelial cells (17). Similarly, IL-6 did not regulate PTX3 mRNA in endothelial, hepatic, or fibroblastic cells (9), mononuclear phagocytes (3), renal epithelial cells (32), or synoviocytes (26).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In fact, a positive effect of both IL-1 and TNF␣ has been observed previously in a wide range of cells: endothelial (9,20) and hepatic cells (9), fibroblasts (9,20,23), myoblasts (20), mononuclear phagocytes (3,20), and renal epithelial cells (32). Furthermore, IL-1 was effective in dendritic (12) and smooth muscle cells (11) and TNF␣ in 3T3-F442A adipocytes (1), synoviocytes (26), and lung epithelial cells (17). Similarly, IL-6 did not regulate PTX3 mRNA in endothelial, hepatic, or fibroblastic cells (9), mononuclear phagocytes (3), renal epithelial cells (32), or synoviocytes (26).…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, PTX3 has different cell-specific gene expression and ligand-binding properties from CRP (8). PTX3 is produced in response to proinflammatory signals by mononuclear phagocytes (3,20), myeloid dendritic cells (12), fibroblasts (9,20,23), endothelial cells (9,20), hepatic cells (9), myoblasts (20), synoviocytes (26), lung epithelial cells (17), renal epithelial cells (32), adipocytes (1), AT-derived mesenchymal stem cells (25), and smooth muscle cells (11). Expression of the PTX3 gene increases in human cultured myotubes compared with the skeletal muscle tissue (38).…”
mentioning
confidence: 99%
“…(1) stimulation of IL-1R induces the transcription of numerous pro-labor genes via MAPK p38, JNK, c-jun and small GTPase Rho in myometrial smooth muscle cells, which results in increased myometrial contractility (Tribe et al 2003, Chevillard et al 2007, Nadeau-Vallee et al 2015b; and preterm labor in mice and non-human primates (Romero et al 1991, Sadowsky et al 2006; (2) antagonism of IL-1R prevents all of these events (Romero & Tartakovsky 1992, Nadeau-Vallee et al 2015b; (3) IL-1α amniotic fluid levels are elevated in women that deliver preterm (Figueroa et al 2005); (4) preterm labor is associated with increased IL-1α activity in amniotic fluids (Romero et al 1989); and (5) maternal polymorphisms and haplotypes in the IL-1α gene (Sata et al 2009), as well as fetal polymorphism in the endogenous IL-1R antagonist (Witkin et al 2003), have been associated with increased risk of preterm birth. The critical role of IL-1 in preterm labor has been reviewed elsewhere (Nadeau-Vallee et al 2015a).…”
Section: Preterm Labormentioning
confidence: 99%
“…In contrast, MafG and MafK mRNA and protein expression are not induced rapidly by these cytokines, hinting at a specific role for MafF in the early inflammatory response. 25,106 Of interest, Nrf2 may also be involved in the regulation of inflammation in vivo. [107][108][109][110] It has been shown that Nrf2 functions downstream of prostaglandins regulating the expression of anti-oxidative stress genes during the acute inflammatory response.…”
Section: A Role In Inflammationmentioning
confidence: 99%